Comparisons of fatty acid accumulation patterns of two filter feeders, Branchinella kugenumaensis and Daphnia magna in a controlled environment - Yang, Dongwoo; Jeong, Seonah; Kim, Jihee; Park, Sangkyu (Journal of Ecology and Environment, 2022)
Background: Filter-feeding zooplankton has limited food resources owing to their hab-itat. Consequently, it is crucial for them to acquire all essential compounds, such as fatty acids (FAs) and amino acids, from confined diets. To elucidate the trophic transfer of FAs to filter feeders, the primary consumers in freshwater ecosystems, we compared the FA accumulation patterns of two species of filter-feeding zooplankton, Daphnia magna and Branchinella kugenumaensis, in a laboratory experiment. Experimental neonates and nau-plii preyed on a single phytoplankton species (Selenastrum capricornutum) for three days after hatching prior to diet switching. Five replicates per feeding group in each species were fed on six different types of mixed phytoplankton diet for 10 days after diet switching. Subsequently, the consumers and diets were harvested and FAs were extracted. Results: Principal component analysis showed that the FA profiles of zooplankton were well-grouped by species and diet. Although diet affects the FA profiles of consumers, they exhibit different FA accumulation patterns. D. magna had a higher 18C-ω3 content and ω3/ω6 ratio than did B. kugenumaensis. In contrast, B. kugenumaensis had higher con-tents of 18:1ω7 and 20:5ω3 (eicosapentaenoic acid), 22:6ω3 (docosahexaenoic acid), and a higher ratio of ∑18C monounsaturated FAs to ∑18C-ω3 polyunsaturated FAs than did D. magna. Conclusions: This study showed that two primary consumers, D. magna and B. kugenu-maensis, fed the same diet had different assimilation patterns of FAs under controlled en-vironments. Specific FA accumulation patterns in filter feeders can provide information on the transfer process of various FAs to high-trophic organisms.
Keywords: 18C MUFAs; 18C-ω3 polyunsaturated fatty acids; Branchinella kugenumaensis; Daphnia magna; Fatty acid; Filter feeder